An effective approach for fabricating high-strength polyurethane hydrogels with reversible photochromic performance as a photoswitch. (23rd March 2021) - Li, Guangyao; Pan, Zhicheng; Jia, Zhanyu; Wang, Juan; Wang, Jianlong; Zhang, Ning; Pan, Mingwang; Yuan, Jinfeng
Abstract : Reversible high-strength photochromic polyurethane hydrogel which can realize information storage was successfully prepared by a polyaddition reaction. Abstract : Photochromic hydrogels have attracted widespread attention due to their potential applications in optical devices. Spiropyran (SP) is one of the most investigated organic photochromic compounds and has high sensitivity towards a wide range of stimuli. However, it generally requires sophisticated chemical modification for its incorporation into hydrogels as a functional monomer. In addition, the relatively poor mechanical property is a key limitation with the use of hydrogels in many applications. Herein, we provide an effective approach to directly incorporate the SP photochromic group into a polyurethane hydrogel without any modification. A new type of photochromic polyurethane hydrogel that has excellent photochromic and mechanical properties was successfully prepared. Due to the isomerization reaction of the reversible Cspiro –O bond provided by SP, the hydrogel demonstrated a noticeable and reversible color change on adjusting the SP content. The incorporation of SP significantly improved the mechanical properties of the PU hydrogel; the tensile strength (3.41 MPa) and the high elastic modulus (4.29 MPa) of the PU-SP hydrogel increased 5.4-fold and 9.5-fold, respectively, as compared to the PU hydrogel under the same –NCO to –OH ratio. Moreover, the PU-SP hydrogel has a good reversible photochromic property, which can easily achieve repeated erasing and rewriting. In summary, our present work provides an effective approach to prepare a high-strength and light-responsive photoswitch polyurethane hydrogel through SP without further chemical modification, which may have broad application prospects in wearable soft sensors, erasable optical displays and artificial intelligence systems.